Evidence of validity in the Orpheus Business Personality Inventory adaptation in Brazil - Jersica Assis Lozado; John Neville Rust; Igor Gomes Menezes (Revista Psicologia)
The purpose of this work was to present evidences of validity for Orpheus Business Personality Inventory to the Brazilian population. Five experts contributed to the investigation of evidence content validity. In total, 938 individuals responded the test. To examine the evidences of construct validity, a Full Information Factor Analysis was carried out. The results of this exploratory study identified a group of items with low factor loadings. Cronbach’s alpha and omega coefficient were calculated to measure reliability in the scales, their values varied from .65 to .77, and from .53 to .77, respectively. Misfit measurements were also deployed using Rasch model all items presented adequate values. Future studies are needed to clearly define the adaptability to the population; however, the quality of the psychometric properties could be testified through evidences of content validity, internal structure and stability test-retest for OBPI, test-retest stability for OBPI, which may be an important selection test in Brazilian organizations.